ANALISIS LINGKUNGAN KELUARGA DISHARMONIS DITINJAU DARI HASIL BELAJAR IPAS SISWA SEKOLAH DASAR - Yunianto, Rifan; Shoufika Hilyana, F.; Arsyad Fardani, Much (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the disharmonious family environment in terms of the high social studies learning outcomes of fourth-grade students of SDN Tondokerto,. The family environment is divided into two, namely harmonious and disharmonious families. A disharmonious family is a condition in which a family cannot carry out its role properly. A disharmonious family has six indicators including spiritual crisis, lack of family knowledge, egocentrism, educational problems, busyness problems, and economic problems. This study is included in the type of qualitative phenomenological research. The subjects in this study were 1 of 18 fourth-grade students of SDN Tondokerto. One student who is a student who has high learning outcomes but lives in a disharmonious family. Data collection techniques used include observation, documentation, and interviews. The validity of the data in this study uses the degree of trust (credibility). Credibility testing is carried out using source triangulation and technique triangulation. Data analysis in this study uses the Miles and Hubberman model which contains data reduction, data presentation, and data conclusions. The results of the study showed that indicators in disharmonious families affect the results of learning science at SDN Tondokerto. AIS is a student who lives in a disharmonious family. However, he has a high enthusiasm for learning and does not pay attention to the shortcomings in his family, so that the results of learning science he obtains are also high. It can be concluded that indicators in disharmonious families affect the results of learning science at SDN Tondokerto. The good or bad impact felt depends on the treatment and how students and parents respond to these indicators.